Assessing the subcellular distribution of oncogenic phosphoinositide 3-kinase using microinjection into live cells. Issue 2 (14th April 2014) - Layton, Meredith J.; Rynkiewicz, Natalie K.; Ivetac, Ivan; Horan, Kristy A.; Mitchell, Christina A.; Phillips, Wayne A.
Abstract : Oncogenic forms of PI3Kα (phosphoinositide 3-kinase α) microinjected into live cells are not recruited to the PM (plasma membrane) to a greater extent, and do not reside at the PM longer, than wild-type PI3Kα. Abstract : Oncogenic mutations in PIK3CA lead to an increase in intrinsic phosphoinositide kinase activity, but it is thought that increased access of PI3Kα (phosphoinositide 3-kinase α) to its PM (plasma membrane) localized substrate is also required for increased levels of downstream PIP3 /Akt [phosphoinositide-3, 4, 5-trisphosphate/also called PKB (protein kinase B)] signalling. We have studied the subcellular localization of wild-type and the two most common oncogenic mutants of PI3Kα in cells maintained in growth media, and starved or stimulated cells using a novel method in which PI3Kα is pre-formed as a 1:1 p110α:p85α complex in vitro then introduced into live cells by microinjection. Oncogenic E545K and H1047R mutants did not constitutively interact with membrane lipids in vitro or in cells maintained in 10% (v/v) FBS. Following stimulation of RTKs (receptor tyrosine kinases), microinjected PI3Kα was recruited to the PM, but oncogenic forms of PI3Kα were not recruited to the PM to a greater extent and did not reside at the PM longer than the wild-type PI3Kα. Instead, the E545K mutant specifically bound activated Cdc42 in vitro and microinjection of E545K was associated with the formation of cellular protrusions, providing some preliminary evidence that changes in protein–protein interactions may play a role in the oncogenicity of the E545K mutant in addition to the well-known changes in lipid kinase activity.